Surface Warming Slowdown With Continued Subsurface Warming in the East Sea (Japan Sea) Over Recent Decades (2000–2014) - Jeong, Yubeen; Nam, SungHyun; Kwon, Jae-Il; Uppara, Umakanth; Jo, Young-Heon (Frontiers in Marine Science, 2022)
The long-term surface warming trend in the East Sea (Japan Sea; ES hereafter) stalled from 2000 to 2014 (−0.05°C yr−1, surface warming slowdown), while the subsurface (100–300°m) warming trend continued (+0.03°C yr−1). To address the processes underlying these contrasting trends in surface and subsurface temperature change, the trends in sea-level anomaly, isopycnal depth, and wind pattern were analyzed using monthly mean ocean reanalysis system 4 (ORAS4) data. During this period, the strengthened northwesterly/northerly wind in the central part of ES is supposed to contribute to a negative (positive) wind stress curl to its west (east), corresponding to an anticyclonic (cyclonic) circulation in the west (east). Furthermore, the induced negative wind stress in the west appears to enhance the northward penetration of East Korean Warm Current (EKWC), the slowdown in its eastward meandering around 38° N from the Korea coast, resulting in warm water accumulation in the west with peak warm anomaly at relatively greater depth compared to peak cold anomaly in the east. Overall, these wind-driven changes in transport from west to east, wind stress curl induced horizontal divergence (convergence) and the associated upwelling (downwelling), causes surface warming to slow and subsurface warming to persist during 2000 to 2014.